An analytical reading of racial discrimination in sport : Case Study : Claudia Rankine’s Citizen: An American Lyric (2014) - Hadjadj, Bouthaina Khadidja; Mekanfes, Khansaa; Hocine, Aicha (University of Ammar Theledji -Laghouat, 2022)
Racism has negatively impacted the life of people who were subjected to racial prejudice and bias in all domains including sport. Sportsmen and Black athletes in particular have faced significant racial barriers in sports, and the combat is still continuing. This paper’s objective was to highlight the question of racism and racist actions in sport in Citizen: An American Lyric (2014).In this research, the descriptive and analytical approaches were adopted to analyze the problem of racism in sport through Rankine’s eyes, and how racist practices affect participation in sport via illustrating the epic of Zinedine Zidane and Serena Williams. Therefore, our study’s findings indicate that although sport is a potential inclusive arena, racism and discriminatory acts in sport are common, and sport community is still witnessing incidences of racial aggressions toward athletes from different races.Moreover, the inclusion of the theme racism as an arguable issue in Rankine’s book Citizen, especially the theme of racism in sport,and using a unique and different style of writing and visual artworks make the reader indulgein the story and experience the events, which makes the book a subject for criticism and interpretations.